PENGARUH BUDAYA ORGANISASI DAN KEPUASAN KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR DINAS PARIWISATA KOTA TERNATE - Muhammad Thahrim; Rachmat Aviandhono2 (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Khairun, 2018)
The purpose of this study is to determine the influence of Organizational Culture and Job Satisfaction on Employee Performance of Ternate City Tourism Office. Sampling using Proportionate random sampling amounted to 41 respondents. The data used are primary and secondary data with data analysis using multiple linear regression. The results showed that Organizational Culture, and Work Satisfaction had a positive and significant effect on employee performance. From these results can be concluded that Organizational culture fun to encourage good work, and high work discipline will improve the performance of employees of Ternate City Tourism Office.